Spatial and temporal variability of chlorophill a in the Peruvian sea using MODISAQUA images - Quezada García, M. G. (2011)
The chlorophill a in the Peruvian sea must be measured by means of remote sensing in the visible range. The objective of the present work is to determine the chlorophill a concentration using MODIS images from the Peruvian sea. The mean monthly concentration maps of chlorophill a of January, February, March and April of 2006 year has been obtained from the MODIS-AQUA images. In each monthly image the chlrophill a concentration is greater near to coastline and decrese gradually far from the coast. In the Northern coast (0-5°S), the chlorophill a vary between 0.05 to 0.5 g/cm3 and it disperse far from the coast. In the Central coast (5°-15°S) the chlorophill a vary between 10 to 30 g/cm3, it’s more dense in the coastline and diminished conform the distance from the coast is increased. In the Southern coast (15°-20°S) the chlorophill a vary between 3 to 5 g/cm3 very near to the coast. From January to April of 2006 year, these values has been diminished slowly due to the seasonal change.